Tambir : Jamur Alam Papua yang Berpotensi sebagai Jamur Konsumsi - Supeni Sufaati; Vita Purnamasari; Verena Agustini; Suharno Suharno (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
Fungi has several role for humankind, one of them is as food. The potency of wild edible mushrooms as a source of nutrition still need to be explored to support national food security. The aim of this study was to determine the composition of nutrient content of wild edible mushroom called Tambir that commonly be consumed as alternative food by local people in Jayapura, Papua. Samples were collected from the traditional market nearby Uncen campus in Waena, Jayapura, Papua. Micro Kjeldahl method was used to analyze the crude protein content, hexane-gravimetry for lipid, spectrophotometry for carbohydrate, and high performance liquid chromatography (HPLC) for amino acid composition. The results showed that this mushroom has 15.74 % crude protein, 2.59 % lipid, 50.17 % carbohydrate and 8 essential amino acids. The chemical value of those eight essential amino acids were more than 100 that means this mushroom has no amino acid limitation. Therefore, Tambir could be a good alternative protein source for local people. Key words: fungi, proteins, local knowledge, Tambir, Papua.